ANALISIS KELELAHAN NEW PROPELLER KAPLAN K4-70 SERIES PADA KAPAL TUGBOAT 1000 HP MENGGUNAKAN METODE COMPUTIONAL FLUID DYNAMICS - Muhammad Fauzan; Adi Wirawan Husodo; Benedicta Dian Alfanda (Proceedings Conference on Marine Engineering and its Application, 2023)
The function of a tugboat is to tow or push other ships in harbors, open seas and rivers or canals. The propeller used should have an age according to the docking schedule, which is 5 years. However, the propeller was damaged before the ship docked. The owner ordered a new type of propeller with the Kaplan K4-70 series type. The loading given the results of the contour pressure on the CFD software is run using a variation of the propeller rotation. The FEM method for obtaining Hot Spot Stress uses the stress that occurs, namely the von Mises stress (equivalent stress). S-N curve to analyze the results of voltage values and cycles. After that, the value of the fatigue life of the propeller itself can be found. From the results of this study there is an influence on the thrust and torque values for each variation where from the running results the greatest value is obtained at 198.53 rpm at 18601.503 N and 3810.881 Nm and 234.24 rpm at 41563.213N and 6585.7302 Nm. The effect of variations in propeller rotation on thrust and torque values is that the greater the propeller rotation, the greater the value of thrust and torque as well. The location of the hot spot stress for each variation is at the root back blade of the propeller. The maximum stress/stress that occurs in the propeller is 198.53 rpm at 12.07 MPa, 238.24 rpm at 34.646 Mpa and for 357.35 rpm at 97.393. The effect of loading is that the greater the rpm/load value, the greater the resulting stress value (Von-Misses). The service life of the propeller is 198.53 rpm with a service life of 300 days for 25.865 years. For 238.24 rpm for 22.43 years and for 357.35 rpm for 14.57 years.